Analisis Hubungan Faktor Pola Makan Dan Stress Dengan Kejadian Gastritis - Ali Husen; Tjandra, Lusiani (Calvaria Medical Journal, 2023)
Introduction: Gastritis is an infection of the mucosal lining of the stomach. Diet can cause gastritis due to inappropriate eating habits such as eating frequently, eating irregularly, and not eating for a long time, so that stomach acid levels increase. In addition, stress can cause hormonal changes in the body, which stimulates stomach cells to produce excessive amounts of acid. The aim of this research is to analyze the relationship between dietary factors and stress and the incidence of gastritis.Method: The type of research used is a literature review which uses previous research originating from national and international journals as a reference for drawing conclusions on research resultsResults: There is a relationship between diet and stress factors with the incidence of gastritisConclusion: Diet has an important role in the health of the digestive system, an unbalanced diet can affect bowel movements. Eating patterns include types of food, frequency of eating, and number or portions of food in a day. Factors that influence eating patterns are economic, socio-cultural, religious, educational and environmental factors. Stress can also trigger gastritis, because it causes increased gastric acid production and gastric peristaltic movements and influences gastritis recurrence. Keywords: Gastritis, Diet, Stress